2018
DOI: 10.1021/acs.jpca.8b03645
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of OCS–HCCCCH and N2O–HCCCCH Dimers: Theory and Experiment

Abstract: The infrared spectra of the weakly bound dimers OCS-HCCCCH, in the region of the ν fundamental band of OCS (2050 cm), and NO-HCCCCH, in the region of the ν fundamental band of NO (2200 cm), were observed in a pulsed supersonic slit jet expansion probed with tunable diode/QCL lasers. Both OCS-HCCCCH and NO-HCCCCH were found to have planar structure with side-by-side monomer units having nearly parallel axes. These bands have hybrid rotational structure which allows for estimates of the orientation of OCS and NO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In the case of both (CO2)2-CO and -N2, we observed two fundamental bands in the CO2 3 region, a stronger (a,c)-type band corresponding to the (CO2)2-Rg bands reported here, and a weak b-type band. 2 Detection of the weak band confirmed that the (CO2)2 dimer subunits in (CO2)2-CO and -N2 are not planar, and calculations indicated that each CO2 unit departs from planarity by about 19°. We searched for the analogous second fundamentals for (CO2)2-Rg, but were not able to observe them.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In the case of both (CO2)2-CO and -N2, we observed two fundamental bands in the CO2 3 region, a stronger (a,c)-type band corresponding to the (CO2)2-Rg bands reported here, and a weak b-type band. 2 Detection of the weak band confirmed that the (CO2)2 dimer subunits in (CO2)2-CO and -N2 are not planar, and calculations indicated that each CO2 unit departs from planarity by about 19°. We searched for the analogous second fundamentals for (CO2)2-Rg, but were not able to observe them.…”
Section: Resultsmentioning
confidence: 85%
“…Here, we report on another family of trimers, namely those containing two CO2 molecules and one rare gas atom. The present work was inspired by our recent studies of the related trimers (CO2)2-CO and (CO2)2-N2, 1,2 whose structures can be described as resembling a CO2 dimer (near planar, staggered) with the CO or N2 aligned along the CO2 dimer C2 symmetry axis. Not surprisingly, it turns out that (CO2)2-Rg trimers have similar structures with the Rg atom located on the symmetry axis, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Much less is known on complexes containing OCS and the second member of the polyyne series, diacetylene. The only study is that of the mixed dimer of H2C4-OCS in the infrared region reported recently by our group [10]. Like H2C2-OCS, H2C4-OCS was found to have a planar structure with nearly parallel monomer units, and with the help of theoretical calculations, it was established that the observed structure is the lowest energy form on the potential energy surface.…”
Section: Introductionmentioning
confidence: 94%
“…The OCS dimer fragment is planar. The c-axis makes an angle of 23 with the equivalent OCS monomers and the plane of OCS dimer fragment is perpendicular to the b-axis.A search to the higher frequency side of the vibrational fundamental of H2C4-OCS dimer[10] resulted in observation of a new band which was assigned to H2C4-(OCS)2. This band was located around 2068.93 cm -1 , which is 3.83 cm -1 below the band origin of the polar OCS dimer[35] and 9.30 cm -1 above the H2C4-OCS fundamental.…”
mentioning
confidence: 99%
“…Since in this work we had to investigate many different clusters and deal with a large number of structures, we modified the computational approach followed in our previous investigations. 21,22 The present procedure is comprised of three distinct steps, each being carried out at a higher level of theory than the previous one.…”
Section: Structural Calculationsmentioning
confidence: 99%